Lived Experiences of Single Mothers On child Upbringing in Western Division in Tororo District. - Scovia Adikini (Uganda Christian University, 2024)
Experiences of Single mothers in child upbringing is very serious matter that recquires multiple approaches in handling it because it not only affect the single mothersbut the children and the next generation after them and even the society at large.Therefore, this dissertation examinesthe socioeconomic determinants osingle motherhood in Tororo District particularly Western division exploring the complex interplay between economic, social and cultural factors that contribute to the pressing issue. Therefore, using one data collection approach, this study contains a qualitative approach of data collection with insights from interviews. The results reveal that social economic factors are the major causes of single motherhood in Western Division. This research contributes to the existing body of knowledge by providing a nuanced understanding of how socioeconomic issues have led to single motherhood, highlighting the need for multidimensional approach to address this issue. The findings inform policy recommendations and interventions aimed at promoting policies that can improve the well being of single mothers in child upbringing in Western Division in Tororo District.